The Relationship between Learning Environment and Academic Performance of Students - Elly Shahrulnizam, Nur Shuhada Najua; Salim, Siti Aisyah (Research in Management of Technology and Business, 2025)
The quality of education in Malaysia has been the focus of numerous governmental initiatives aimed at meeting global standards and producing competitive graduates. Despite these efforts, academic performance in Malaysian higher education institutions, including Universiti Tun Hussein Onn Malaysia (UTHM), remains inconsistent and often falls below expectations. The learning environment is recognized as a crucial factor influencing students’ academic performance, encompassing both physical aspects, such as facilities and class environment, and social aspects, such as interactions with peers and lecturers. However, challenges persist, as the impact of the learning environment on academic outcomes is not sufficiently explored in the Malaysian higher education context. Existing studies have primarily concentrated on individual factors like socioeconomic status or teaching strategies, leaving a gap in understanding how the overall learning environment affects academic performance. Addressing this gap is essential for designing effective interventions to enhance education quality. This study aims to investigate the relationship between the learning environment and academic performance among UTHM students. A quantitative research approach was employed, with data collected via an online survey from 267 respondents. Analysis using the Statistical Package for Social Science (SPSS) software revealed a significant positive relationship between all variables, with the class environment showing the strongest correlation (coefficient of 0.842). These findings highlight the importance of optimizing the learning environment to improve motivation, interest, and academic success. The study offers practical recommendations for policymakers and educators to enhance learning conditions in Malaysian higher education.